Pengendalian Mutu Produk Daging Ayam Setengah Jadi Menggunakan Metode Statistical Quality Control (SQC) di PT Exotic Group Concept - Austin, Elvin; Priambadi, I Gusti Ngurah; Utami , Ni Made Cyntia (Blantika: Multidisciplinary Journal, 2025)
[Quality Control of Semi Finished Chicken Meat Products Using Statistical Quality Control (SQC) Method at PT Exotic Group Concept] In the manufacturing industry, quality control plays a vital role in ensuring consistent product quality. PT Exotic Group Concept, a company in the Food and Beverage sector, faces a high defect rate issue, particularly in semi-processed chicken meat, which reached 21% during the September–November 2024 period significantly exceeding the company’s acceptable limit of 3%. This condition potentially disrupts warehouse operations and causes financial losses. This study aims to analyze the quality control process at PT Exotic Group Concept using the Statistical Quality Control (SQC) method and to provide sustainable improvement recommendations. The research employed direct observation and documentation, with data processed using the seven quality control tools: check sheet, histogram, pareto diagram, control chart, and fishbone diagram. The results revealed that the main types of defects were vacuum plastic and leaking sealers, caused by human error, the use of thin plastic materials, and uncalibrated machines. After implementing the proposed improvements, the defect rate decreased by 15%, from 21% to only 6%. This study concludes that the application of SQC provides an effective solution to reduce product defects when applied continuously and consistently.